2021
DOI: 10.3390/educsci11030089
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Pre-Service Biology Teachers’ Diagnostic Competences: Relationships between Professional Knowledge, Diagnostic Activities, and Diagnostic Accuracy

Abstract: Teachers’ diagnostic competences are essential with respect to student achievement, classroom assessment, and instructional quality. Important components of diagnostic competences are teachers’ professional knowledge including content knowledge (CK), pedagogical knowledge (PK), and pedagogical content knowledge (PCK), their diagnostic activities as a specification of situation-specific skills, and diagnostic accuracy. Accuracy is determined by comparing a teacher’s observation of classroom incidents with subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 76 publications
1
25
0
4
Order By: Relevance
“…To put this in perspective, knowledge of students' difficulties and frequent sticking points can help teachers design lessons in a student-oriented way (cf., [174]). Studies on subject-specific teaching quality in biology with respect to diagnostic competencies have shown that PCK and PK are statistically significantly related to preservice teachers' diagnostic activities, and biology teachers' PCK is positively related to diagnostic accuracy [95]. Teachers are expected to provide students with learning opportunities that help them develop 21st-century skills, including core competencies in subject areas such as science.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To put this in perspective, knowledge of students' difficulties and frequent sticking points can help teachers design lessons in a student-oriented way (cf., [174]). Studies on subject-specific teaching quality in biology with respect to diagnostic competencies have shown that PCK and PK are statistically significantly related to preservice teachers' diagnostic activities, and biology teachers' PCK is positively related to diagnostic accuracy [95]. Teachers are expected to provide students with learning opportunities that help them develop 21st-century skills, including core competencies in subject areas such as science.…”
Section: Discussionmentioning
confidence: 99%
“…Results of path analyses utilising Rasch measures showed that both PCK and PK were statistically significantly in relation to pre-service teachers' diagnostic activities. Additionally, biology teachers' PCK was positively related to diagnostic accuracy [95].…”
Section: Relevance Of Diagnostic Competencies For (Pre-service) Teachersmentioning
confidence: 96%
See 2 more Smart Citations
“…Hier stellten Krauss et al (2020) fest, dass Fragebogenformate vor allem das deklarative Wissen fokussieren, wohingegen mithilfe von Videovignetten eher situationsspezifische Fähigkeiten und Fertigkeiten erfasst werden können (Blömeke et al 2015;Lindmeier 2010, Kaiser et al 2015. Kramer et al (2021) konnten bspw. Zusammenhänge zwischen den Facetten des Professionswissens, erhoben über einen Fragebogen, und den gezeigten diagnostischen Aktivitäten, erfasst mit einer videobasierten Klassenraumsituation, angehender Biologie-Lehrkräfte nachweisen.…”
Section: Introductionunclassified